Hybrid Skyhook-Stability Augmentation System For Ride Quality Improvement Of Railway Vehicle - Harun, Mohd Hanif; W. Abdullah@Zakaria, W. Mohd Zailimi; Jamaluddin, Hishamuddin; Ab Rahman, Roslan; Hudha, Khisbullah (Trans Tech Publications, 2014)
This paper is aimed to show the improvement of ride quality of railway vehicle with semi-active suspension systems.The dynamics of nine degrees-of-freedom (9-DOF) railway vehicle model is developed consists of a vehicle body,two bogies and four wheel-set.The disturbance considered is track irregularity which is modelled as a sine wave.The control algorithm for the semi-active suspension system is developed based on Stability Augmentation System (SAS) integrated with skyhook controller to reduce the effect of track disturbance.The performances of passive and semi-active suspension are compared by simulation using MATLAB-SIMULINK software. The results of the study show that the proposed controller is able to significantly improve ride quality of railway vehicle body.It is also noted that the additional ride control loop which is skyhook control is able to further improve the performance of SAS controller for the system.